Abydos / Umm el-Qaab, Ägypten. Aufarbeitung der Arbeiten in den prädynastischen und frühzeitlichen Königsgräbern - Köhler, Eva Christiana (e-Forschungsberichte des DAI, 2017)
The team working with material from the Predynastic Cemetery U and the Early Dynastic royal tombs at Abydos is currently focusing on preparing the publications of material which had been excavated under the direction of G. Dreyer, and conducted a two weeks study season in the field. The work concentrated on the archaeo-botanical analysis of wood and plant remains, the study of matting and basketry and on the documentation of early pottery.